Population Management of Samia cynthia ricini Boisduval (Lepidoptera: Saturniidae) by Eggs Refrigeration and Its Effect on Hatchability, Development, and Fecundity - Ihsan Nurkomar; Dina Wahyu Trisnawati; Narisara Piyasaengthong; Putri Nafisah Kirana (Bogor Agricultural University, Indonesia, 2023)
Egg viability, hatchability, and development are significant factors in the natural silk industry. Life cycle modification is an important aspect that must be considered to perform effective and efficient mass-rearing and quality control. This study aimed to improve the mass rearing efficiency of Samia chintya ricini through a life cycle modification technique by refrigeration. The study was conducted by storing S. c. ricini eggs in the refrigerator at a temperature of 5°C for one to seven days. Observations were made on the hatchability, development time, cocoon shell weight, and adult female fecundity. The results showed that the egg refrigeration period affected the hatchability of the eggs. A more extended period of egg refrigeration significantly decreased hatchability. The eggs could develop into adult insects after being stored for one to five days. Meanwhile, none of the eggs hatched successfully after going through a cold storage period of six and seven days. Furthermore, the egg refrigeration period affected the development time of the egg, larvae, pupae, and adult. A more extended period of egg refrigeration results in slower egg and larval development time. But a faster cocoon development time. The refrigeration period did not significantly affect the cocoon shell weight. However, it was affecting adult female fecundity. Total fecundity decreased as the refrigeration period increased with different daily oviposition patterns. This study implies that when the egg population is excessive, the life cycle of S. c. ricini can be delayed for 1-5 days. This method can be implied as a simple life cycle modification technique for eri silkworm cultivation.